The Influence of Adverse Climate Regions on The Complication of Hypertension Disease (Eurasian Research Bulletin, 2023)
170 hypertensive patients living in regions with adverse climate were examined. All patients underwent subjective, objective, clinical-instrumental and laboratory tests. Changes in arterial blood pressure in patients with different air temperature and humidity in all seasons of the year, their complications and effectiveness of preventive measures were studied.